Structure change of Yb-156 at high-spin states - Hua Hui; Li Zhong-Yu; Wang Shou-Yu; Meng Jie; Li Zhi-Huan; Li Xiang-Qing; Xu Fu-Rong; Liu Hong-Liang; Zhang Shuang-Quan; Zhou Shan-Gui; Ye Yan-Lin; Jiang Dong-Xing; et al. (CHINESE PHYSICS C, 2009)
{{High-spin states of Yb-156 have been studied via the Sm-144(O-16,4n)Yb-156 fusion-evaporation reaction at beam energy 102 MeV. The positive-parity yrast band and negative-parity cascade have been extended up to higher-spin states, respectively. The characteristics of the negative-parity sequence above the 25 state may related to the excitation from the nucleon in the Z = 64